Attitudes of Health Workers towards People with Mental Health Problems in Mosul City / Iraq - Eman Salem AL-Khafaf (Kufa Journal for Nursing Sciences)
Objective: The main objectives of this research were to survey the attitudes of Iraqi Health workers towards mentally ill people in Mosul city in Iraq and to investigate possible factors, which impact on Iraqi health workers' attitudes to people with mental health problems.